Institutions, paradoxes, and compensation logics: evidence from corporate values of the largest Chinese and US companies. Issue 5 (20th October 2018) - Cardona, Pablo; Malbašić, Ivan; Rey, Carlos
ABSTRACT: This study introduces the concept of Institutional Compensation Logics, which suggests that organizations can dynamically balance coexisting local and global logics, through a process known as the 'paradox of embedded action'. Through this process, managers can gradually adapt institutional logics to the global environment, even if their actions, intentions, and rationality are embedded in the very logics that they wish to change. We propose that one important way they do that is by designing corporate values that challenge the organization's local values. To test this approach, we use the mission-based corporate values' framework and analyse the corporate values of a sample from the largest Fortune companies in the two most influential world economies: China (PRC) and the United States (US). Our study also helps advance the understanding of how espoused values are related to cultural values, often in paradoxical ways, thus supporting a negative relationship between espoused organizational and cultural values.